Parâmetros genéticos dos caracteres da qualidade nutricional do feijão: fibra alimentar e aminoácidos sulfurados - Londero, Patricia Medianeira Grigoletto (2008)
The common bean (Phaseolus vulgaris L.) have high content of dietary fiber and protein of high quality, so it can be considered a functional food. The objectives of this work were: (1) to verify if occurs maternal effect for the insoluble fiber, soluble fiber, methionine and cysteine content in grains common bean; (2) to estimate the heritability and gain from selection for these traits; (3) to assess the composition of amino acids of early generations of common bean obtained from controlled crosses with genitor of high cysteine content. Six generations were obtained (F1, F1 reciprocal, F2, F2 reciprocal, retrocruzamento 1 - RCP1 and retrocruzamento 2 - RCP2) from crosses between genitors contrasting to the insoluble fiber (Guateian 6662 x Guapo Brilhante), soluble fiber (Guapo Brilhante x Pérola), methionine (BRS Valente x Iapar 44) and cysteine (TPS Nobre x Minuano) content. The soluble and insoluble fiber contents were determined by enzyme-gravimetric method and the amino acids content were determined by high performance liquid chromatography (HPLC). The experimental design was a completely randomized, with variable number of replications for generations obtained. The results showed presence of genetic variability for the insoluble fiber, methionine and cysteine contents. No was observed effect maternal significant for insoluble fiber, soluble fiber, methionine and cysteine contents in grains of common bean. Estimates of heritability moderate in the broad sense of 45.22% and gain from selection predicto of 10.15% was obtained for the insoluble fiber. Unable to estimate the heritability in the broad sense and in the narrow sense for soluble fiber, because of lack of genetic variability in different generations, and for the methionine and cysteine content, because genetic negative variances were obtained. The selection of plants F2 obtained from crosses between Guateian 6662 x Guapo Brilhante and between BRS Valente x Iapar 44 may result in superior genotypes for the insoluble fiber and methionine content, respectively. The genitors TPS Nobre and Minuano and F1 and F1r generations showed essential amino acids and nonessential contents suitable for use in food. For the cysteine content, it is not possible to select any plant in the F2 generation due to the low contents of this amino acid sulfur.